Effectiveness of Counseling for Infertile Couples on Women's Emotional Disturbance: A Randomized Clinical Trial - Sorkhani, Tayebeh Mokhtari; Ahmadi, Atefeh; Mirzaee, Moghaddameh; Habibzadeh, Victoria; Alidousti, Katayoun (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective The psychosocial burden of infertility among couples can be one of the most important reasons for women's emotional disturbance. The goal of the present study was to investigate the effect of counseling on different emotional aspects of infertile women.Methods The present randomized clinical trial was performed on 60 couples with primary infertility who were referred for treatment for the first time and did not receive psychiatric or psychological treatment. Samples were allocated to an intervention group (30 couples) and a control group (30 couples) by simple randomization. The intervention group received infertility counseling for 6 45-minute sessions twice a week, and the control group received routine care. The Screening on Distress in Fertility Treatment (SCREENIVF) questionnaire was completed before and after the intervention. Samples were collected from November to December 2016 for 3 months. For the data analysis, we used the Statistical Package for the Social Sciences (IBM SPSS Statistics for Windows, IBM Corp., Armonk, NY, United States) software, version 19.0, and the paired t-test, the independent t-test, the Mann-Whitney test, the Wilcoxon test, and the Chi-squared test.Results The mean age of the participants was 33.39 ± 5.67 years. All studied couples had primary infertility and no children. The mean duration of the couples' infertility was 3 years. There was a significant difference regarding depression (1.55 ± 1.92; p < 0.0001), social support (15.73 ± 3.41; p < 0.0001), and cognitions regarding domains of fertility problems (26.48 ± 3.05; p = 0.001) between the 2 groups after the intervention, but there was no significant difference regarding anxiety (25.03 ± 3.09; p = 0.35).Conclusion The findings showed that infertility counseling did not affect the total score of infertile women' emotional status, but improved the domains of it except, anxiety.
Keywords: infertility; emotion; social support; anxiety; depression; counselling